FORMULATION AND EVALUATION OF MELOXICAM MICROSPHERES FOR COLON TARGETED DRUG DELIVERY - DHAS, SHRADHA KISHOR; DESHMUKH, GANESH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The objective of this research was to organize and evaluate colon specific microspheres of the meloxicam for the treatment of colorectal cancer. Methods: Sodium alginate microspheres were prepared by ionotropic gelation method using different ratios of meloxicam and sodium alginate (1:1, 1:2, and 1:3). Eudragit-coating of meloxicam, sodium alginate microspheres was performed by coacervation phase separation technique. Results: The microspheres were characterized by shape, particle size, size distribution, incorporation efficiency, in vitro drug release studies and stability studies. The outer surfaces of the core and coated microspheres, which were spherical in shape, were rough and smooth, respectively. The size of the core microspheres ranged from 20 to 52 μm, and therefore the size of the coated microspheres ranged from 107 to 178 μm. The core microspheres sustained the discharge for 10 h during a pH progression medium mimicking the condition of gastrointestinal tract. The release studies of coated microspheres were performed during a similar dissolution medium as mentioned above. In acidic medium the discharge rate was much slower, however the drug was released quickly at pH 7.4 and their release was sustained up to 24 h. Conclusions: It’s concluded from this investigation that Eudragit-coated sodium alginate microspheres are promising controlled release carriers for colon-targeted delivery of meloxicam.